Selective miRNA inhibition in CD8+ cytotoxic T lymphocytes enhances HIV-1 specific cytotoxic responses - Madrid-Elena, Nadia; Serrano-Villar, Sergio; Gutiérrez, Carolina; Sastre, Beatriz; Morín, Matías; Luna, Laura; Martín, Laura; Santoyo-López, Javier; López-Huertas, María Rosa; Moreno, Elena; García-Bermejo, María Laura; Moreno-Pelayo, Miguel Ángel; et al. (Frontiers in Immunology, 2022)
miRNAs dictate relevant virus-host interactions, offering new avenues for interventions to achieve an HIV remission. We aimed to enhance HIV-specific cytotoxic responses—a hallmark of natural HIV control— by miRNA modulation in T cells. We recruited 12 participants six elite controllers and six patients with chronic HIV infection on long-term antiretroviral therapy ("progressors"). Elite controllers exhibited stronger HIV-specific cytotoxic responses than the progressors, and their CD8+T cells showed a miRNA (hsa-miR-10a-5p) significantly downregulated. When we transfected ex vivo CD8+ T cells from progressors with a synthetic miR-10a-5p inhibitor, miR-10a-5p levels decreased in 4 out of 6 progressors, correlating with an increase in HIV-specific cytotoxic responses. The effects of miR-10a-5p inhibition on HIV-specific CTL responses were modest, short-lived, and occurred before day seven after modulation. IL-4 and TNF-α levels strongly correlated with HIV-specific cytotoxic capacity. Thus, inhibition of miR-10a-5p enhanced HIV-specific CD8+ T cell capacity in progressors. Our pilot study proves the concept that miRNA modulation is a feasible strategy to combat HIV persistence by enhancing specific cytotoxic immune responses, which will inform new approaches for achieving an antiretroviral therapy-free HIV remission.